2017
DOI: 10.1007/s10750-017-3423-9
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope discrimination factors of omnivorous fishes: influence of tissue type, temperature, diet composition and formulated feeds

Abstract: Application of stable isotope data to trophic studies requires understanding of factors influencing the isotopic discrimination factor (D) between consumers and their prey resources. This is missing for many omnivorous species, despite their diet and environment potentially impacting D. The effects of temperature, diet (including formulated feeds) and tissue type on D 13 C and D 15 N were thus tested experimentally. A temperature experiment exposed three species to identical diets at 18 and 23°C, whereas a die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…A consistent effect of temperature on carbon tissue-diet isotopic spacing has been observed in previous studies, in which isotopic spacing increases with increasing temperature (Barnes et al 2007;Britton and Busst 2018). Although we found differences in d 13 C in muscle and heart tissues among temperature groups, the pattern did not represent a systematic change and was not significant.…”
Section: Trends Of Otolith Isotope Values In Relation To Temperaturesupporting
confidence: 87%
See 4 more Smart Citations
“…A consistent effect of temperature on carbon tissue-diet isotopic spacing has been observed in previous studies, in which isotopic spacing increases with increasing temperature (Barnes et al 2007;Britton and Busst 2018). Although we found differences in d 13 C in muscle and heart tissues among temperature groups, the pattern did not represent a systematic change and was not significant.…”
Section: Trends Of Otolith Isotope Values In Relation To Temperaturesupporting
confidence: 87%
“…Barnes et al (2007) found a negative relationship between Dd 15 N values and temperature (4.41% at 118C and 3.78% at 168C) in white muscles of European sea bass. However, Britton and Busst (2018) found a positive relationship between tissue-diet isotopic spacing and temperature (18 v. 238C). Britton and Busst (2018) experimented with three species of Cyprinidae, and found significantly higher tissue-diet isotopic spacing at the highest temperature for all tissues analysed (muscle, fin and scale).…”
Section: Trends Of Otolith Isotope Values In Relation To Temperaturementioning
confidence: 84%
See 3 more Smart Citations